Culture and entrepreneurial intention among students of Universiti Malaysia Sabah - Nurul Ain Abdullah (2011)
Issue of imbalance growth economics between ethnics in Malaysia has long been a central development issue. Rate of emergence of entrepreneurs between ethnicities in the country is one of the best predictor to the issue. This gap could be influenced by the ethnics' culture. Hence, this study is conducted to determine the students' ethnics' cultural difference on the entrepreneurial intention. The elements of culture included are based on the five Hofstede's cultural dimensions; uncertainty avoidance, power distance, collectivism, masculinity, and long term orientation. Survey methods by Yoo, Donthu, and Lenartowicz (2011) (CVScale) and by Linan and Chen (2006 (Entrepreneurial Intention Questionnaire) were used on a population of potential entrepreneurs such as students. By employing convenient sampling, the data was gathered from the respondents studying in University Malaysia Sabah. The study has used SPSS 17 to investigate data and to test developed hypotheses. It was found that uncertainty avoidance, masculinity and long-term orientation are effecting on the growth of entrepreneurial intention in the context of the students of University Malaysia Sabah. Findings of this study would be beneficial to policy makers, practitioners and researchers.